A multimodal imaging analysis of subcortical gray matter in fragile X premutation carriers. Issue 9 (6th May 2013) - Wang, Jun Yi; Hagerman, Randi J.; Rivera, Susan M.
ABSTRACT Approximately 40% of males with the fragile X premutation develop fragile X–associated tremor/ataxia syndrome after age 50. Although the thalamus and basal ganglia play a crucial role in movement disorders, their involvement in fragile X premutation carriers has not been systematically investigated. The current study characterized structural abnormalities associated with fragile X premutation carriers (with and without fragile X–associated tremor/ataxia syndrome) in the thalamus, caudate nucleus, putamen, and globus pallidus using T1‐weighted and diffusion tensor imaging. Male premutation carriers with fragile X–associated tremor/ataxia syndrome showed significant volume atrophy and diffusion‐weighted signal loss in all 4 structures compared with the control group. They also exhibited volume atrophy and diffusion‐weighted signal loss in the thalamus and striatum compared with the premutation carriers without fragile X–associated tremor/ataxia syndrome. Importantly, many of the measurements exhibited robust correlations with symptom severity, with volume and diffusion‐weighted imaging measurements displaying negative correlations and fractional anisotropy measurements displaying positive correlations. The current study demonstrated involvement of all 4 subcortical gray matter structures in fragile X–associated tremor/ataxia syndrome, with significant volume atrophy, and possible iron deposition indicated by the diffusion‐weighted signal loss. The significant correlation between the subcortical measurements and symptom severity suggests the benefits of tracking structural changes in subcortical gray matter in future longitudinal studies for early detection and disease monitoring. © 2013 Movement Disorder Society